Micromechanical and experimental analysis of mechanical properties of graphene/CNT epoxy composites. (2020) - Nagar, Sumit; Sharma, Kamal; Kukreja, Nitin; Shukla, Manoj Kumar
Abstract: Amine functionalized multilayer graphene (Af -MLG) and amine functionalized multi wall carbon nano tube (CNT) (Af -MWCNT) were fabricated by sonication method, maintaining the ratio of both the nano fillers as 1:1 and were termed as hybrid fillers due to its composition. The effects of both these fillers on the mechanical properties of epoxy composites were researched upon. Hybrid composite samples were characterized using Scanning electron microscope (SEM) for morphology study. The mechanical behaviour of graphene reinforced epoxy based composites (Gr/Ep-C) were studied using continuum based micromechanical models such as Halpin –Tsai (H-T) and Mori –Tanaka (M−T). The mechanical properties were depicted graphically. The variation in properties have been evaluated with respect to filler weight fraction and aspect ratio using a well defined MATLAB code. The ratio of longitudinal and transverse modulus to the modulus of matrix was then plotted with weight fraction and aspect ratio. When weight fraction and aspect ratio were increased from 0 to 10% and 0–1000 for H-T and M-T models an expected enhancement in the ratio of longitudinal modulus to the modulus of matrix was noticed.